THE PRINCIPAL'S STRATEGY IN IMPLEMENTING PLANNING AND ORGANIZING TO IMPROVE THE QUALITY OF EDUCATION IN SMKN 1 PLUPUH - Awalia Rina Rahmawati; Bambang Sumar Djoko (STKIP Pesisir Selatan, 2025)
This study analyzes the effectiveness of the planning and organizing strategies implemented by the Principal of SMKN 1 Plupuh. The main focus is evaluating data-based strategic management and strengthening work culture to achieve National Education Standards (SNP) to improve the quality of school education. A qualitative approach with a case study method was used. Data collection was carried out through in-depth interviews with the Principal and management team, direct observation of managerial activities, and document studies of quality report cards and the School Budget Work Plan. Data analysis compares field practices with POAC educational management theory. Findings indicate that planning begins with team coordination for data-based quality report card analysis and program priorities. Organizational development involves the formation of adaptive functional work teams such as the Internal Quality Assurance Team, with clear delegation of authority, SOPs, and job descriptions. Despite success, challenges include limited budgets from BOS/BOP funds and the consistency of the monitoring system. The novelty of this research is the integration of digital quality report card-based planning analysis with the collaborative work culture typical of SMKN 1 Plupuh Sragen Regency.